Structure of Al-Ge-Ni melts along the Al60Ge40 – Al60Ni40 section - Яковенко, О.; Півницька, В.; Казіміров, В.; Роїк, О.; Сокольський, В. (Київський національний університет імені Тараса Шевченка, 2016)
X-ray diffraction study and Reverse Monte Carlo methods have been used to carry out a complex investigation of structure of Al-Ge-Ni melts along the section Al60Ge40–Al60Ni40. The experimental intensity curves have been obtained at temperatures near the liquidus line and at 1350°C. The structure factors (SF) and pair distribution functions (PDF) of the melts have been calculated. SF curves show the gradual transformation with increase in Ni content: a shift of the maximums to higher Q-values and significant increase of the height of first maximum, along with increase of height the first maximum of the PDF curves. An asymmetry of the first maximum of SF for Al61Ge28.5Ni10.5 melt, which is consistent with position of first maximum of SF for liquid germanium, points out presence of clusters with liquid germanium structure. With growth of temperature to 1350°C the shape of the first SF maximum is smoothed while position is shifted to lower Q-values in consequence of higher structure homogeneity of the melts. The structure models of investigated melts have been constructed by means of RMC method. The basic cubic cell contained 104 particles with stoichiometric compositions; atomic number density of a melt and cut-off distances have been used as restrictions. An analysis of bond-angle distribution functions for atoms in obtained models shows an increase in level of structural organisation of local atomic structure with increase of Ni content. The concentration dependence of mathematical expectations and standard deviations of coefficient of sphericity for Voronoi polyhedra indicate an intensive interaction in Al-Ni and Ge-Ni pairs, leading to a significant impact of Ni atoms on formation of local atomic structure. As Ksph for VP around Al atoms in Al61Ge15Ni24 melt reach an extreme value, a presence of clusters with composition, close to compound Ni5Ge3, have suggested.

Рентгенодифракційним методом та методом оберненого Монте-Карло проведено комплексне дослідження структурирозплавів системи Al-Ge-Ni вздовж перерізу Al60Ge40 – Al60Ni40. Встановлено суттєвий вплив нікелю на формування атомноїструктури потрійних розплавів, що обумовлено інтенсивною взаємодією атомів в парах Al-Ni та Ge-Ni, показано існуваннямікроугрупувань рідкого германію в розплаві складу Al61Ge28,5Ni10,5 та мікроугрупувань, близьких за складом до інтерметаліду Ni5Ge3 в розплаві складу Al61Ge15Ni24.
Структура розплавів Al-Ge-Ni вздовж перерізу Al60Ge40 – Al60Ni40
Keywords: Al-Ge-Ni liquid alloy; Reverse Monte Carlo method; local melt structure; розплав Al-Ge-Ni; метод оберненого Монте Карло; локальна структура розплаву; -